2018
DOI: 10.1128/aem.02865-17
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation and Dissolution of Magnetite Crystals in a Magnetically Responsive Ciliate

Abstract: Magnetotactic bacteria (MTB) represent a group of microorganisms that are widespread in aquatic habitats and thrive at oxic-anoxic interfaces. They are able to scavenge high concentrations of iron thanks to the biomineralization of magnetic crystals in their unique organelles, the so-called magnetosome chains. Although their biodiversity has been intensively studied, their ecology and impact on iron cycling remain largely unexplored. Predation by protozoa was suggested as one of the ecological processes that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 65 publications
4
20
0
1
Order By: Relevance
“…In this study, it was not possible to state if this behaviour occurs in environmental conditions and if magnetoreception could arise from the interaction. Recently, this behaviour was investigated in natural populations of protists and MTB, and it was shown that ciliates affiliated to the genus Uronema (Stramenopiles-Alveolates-Rhizaria, SAR group) were able to ingest hundreds of MTB into acidic vacuoles to progressively become sensitive to the variations of the magnetic fields in the same way than MTB (Figure 2A and B) [11]. The magnetic response in MTB-grazers is certainly not encoded in the eukaryote genome, but this behaviour seems to facilitate movement of grazers towards the prey biomass.…”
Section: Magnetically Responsive Protozoan Grazersmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, it was not possible to state if this behaviour occurs in environmental conditions and if magnetoreception could arise from the interaction. Recently, this behaviour was investigated in natural populations of protists and MTB, and it was shown that ciliates affiliated to the genus Uronema (Stramenopiles-Alveolates-Rhizaria, SAR group) were able to ingest hundreds of MTB into acidic vacuoles to progressively become sensitive to the variations of the magnetic fields in the same way than MTB (Figure 2A and B) [11]. The magnetic response in MTB-grazers is certainly not encoded in the eukaryote genome, but this behaviour seems to facilitate movement of grazers towards the prey biomass.…”
Section: Magnetically Responsive Protozoan Grazersmentioning
confidence: 99%
“…However, the directed grazing towards these preys specifically and the magnetic response suggest that this interaction is widespread among marine and freshwater heterotrophic flagellates and ciliates ( Figure 2). MTB-grazers seem to have evolved different strategies for the internalization of MTB and their magnetosome chains: (i) sequestration in food vacuoles (Figure 2A and B), (ii) accumulation in a specific location in the cell ( Figure 2C and D), and (iii) an apparently random storage in the cell (Figure 2E) [11,48,50]. These magnetically responsive protists also appear to have evolved different strategies to deal with iron toxicity with (i) the egestion of magnetic inclusions where magnetosomes accumulated [48] and (ii) the progressive dissolution of magnetosomes until the colloidal iron would be expelled from the protistan cell via the cytoproct [11,50,51].…”
Section: Magnetically Responsive Protozoan Grazersmentioning
confidence: 99%
See 1 more Smart Citation
“…In one type, they appeared to be in vacuoles and were extruded from the cell without apparent harm, although no longer displaying magnetotaxis. Further analysis of those magnetic protists revealed that magnetosome‐like structures found inside these organisms were identical to those found in MTB present in the same environment (Bazylinski et al ., ), suggesting that the magnetosome‐like structures were not biomineralized by the protists but accumulated inside the cells through ingestion of MTB (Monteil et al ., ). Torres de Araujo and colleagues () described a single‐celled eukaryotic alga presenting a magnetotactic behaviour more typical of MTB.…”
Section: Introductionmentioning
confidence: 99%
“…MTB are prey for protozoa, and this is one of the likely pathways for return of iron to the environment (Bazylinski, et al 2000, Lin, et al 2014a, Monteil, et al 2018. In Lvdao Lake the digestion of magnetosomes in the food vacuoles of protozoa during grazing on MTB could generate bioavailable iron for cyanobacteria.…”
Section: Discussionmentioning
confidence: 99%